PROSPECTS AND PROBLEMS OF INNOVATIVE DEVELOPMENT OF THE KARACHAY-CHERKESS REPUBLIC - A. Lezhebokov; E. Sergodeeva (Вестник Северо-Кавказского федерального университета, 2022)
The paper considers the prospects of socio-cultural development of the innovative sphere of the Karachay-Cherkess Republic. Based on the conducted sociological research and analysis of statistical data, the high personnel, scientific, technical and resource potential of modernization of the leading industries of the region is determined. The comparison of the leading characteristics of innovative development in the context of the subjects of the North Caucasus Federal District, which shows a low level of introduction and use of advanced technologies, is carried out. The data of the Rating of innovative development of the Russian Federation in the context of subjects in relation to Karachay-Cherkessia are analyzed and the discrepancy between the existing potential and the use of innovations in the practice of organizations is shown. On the basis of a sociological study, the presence of a complex of socio-cultural attitudes of the population that hinder the growth of innovative activity is determined.